Protecting Migrant Workers: The Legal Role of Village Governments Through Service Centers - Sutrisno RS; Moh. Ali Syaifudin Zuhri (Rechtenstudent, 2024)
This study aims to analyze the role of village autonomy in providing protection for migrant workers through local policies based on community needs. Villages, as the smallest government entities, have the original authority to regulate and manage community interests based on local social and cultural conditions. Within the framework of decentralization as stipulated in Law Number 23 of 2014, villages have complete autonomy and are not delegated to the central government. However, the implementation of village autonomy faces structural challenges, particularly in the aspect of village finances, which are unbalanced between income and expenditure. This study highlights the Village Regulation policy on the Integrated Service Center for Migrant Worker Villages (Desbumi) as a form of local innovation in protecting migrant workers, especially female workers. Desbumi emerged from a collective awareness of the importance of village involvement from the early phases of labor migration. This study uses a descriptive qualitative approach with case studies of Desbumi implementing villages. The results show that this initiative increases the active role of villages in documentation, assistance, and advocacy for migrant workers. Collaboration between village governments, civil society organizations, and migrant worker communities is key to the policy's success in strengthening social protection functions at the village level.